Akibat Hukum Pekerja Anak Menurut Undang-Undang Nomor 13 Tahun 2003 - I Gusti Ngurah Winda Aditya Putra; I Nyoman Putu Budiartha; Luh Putu Suryani (Warmadewa Press, 2021)
Children who are born into this world will automatically become the successor of the nation and become the pride of their parents. However, the economic difference between each child and their parents causes many of them to work from an early age and even decide to stop taking education to meet their needs. This study aims to analyze the legal consequences of employing children from a legislative perspective. This study uses a normative legal research method, which is literature law which refers to the legal norms contained in statutory regulations. The results of the study show that any work done by a child cannot be separated from the supervision of the parents and has received permission from the parents. A good education makes the nation's successors broaden the knowledge they have that can be used later when doing a job. Employing a minor child is an offender who can be given a criminal sanction of happiness that is snatched when the child is already doing work, making the child become mentally retarded or thought and his age is no longer compatible.